Mapping the socio-political landscape of heat mitigation through urban greenspaces: the case of Taipei Metropolis. (October 2019) - Mabon, Leslie; Shih, Wan-Yu
We assess socio-political challenges for urban heat island (UHI) mitigation in greenspace planning, focusing on Taipei Metropolis, Taiwan. Through analysis of articles from two newspapers, we suggest that attention to greenery and heat tends to reflect immediate weather or planning considerations, and that there is a persistent perception of greenspace as a barrier to economic development. Broad-based, durable rationales extending beyond climate adaptation benefits may be required to sustain support for greenspace planning in Taipei. There is also a need to raise decision makers' awareness of the specific actions required to realize cooling benefits via greening. We argue that the Taipei case demonstrates the potential for policy messaging based on greenspace functions to attain cross-sectoral buy-in for greenspace development or preservation, but that planners and policymakers must ensure that consensus-based governance actually delivers cooling benefits to citizens. Our results also indicate that greenspace planning policy could more explicitly address community-level greening specifically targeted at cooling or other climate adaptation challenges.